1988
DOI: 10.1083/jcb.106.4.1193
|View full text |Cite
|
Sign up to set email alerts
|

Localization of kinesin in cultured cells.

Abstract: Abstract. Kinesin was isolated from bovine brain and used to elicit polyclonal antibodies in rabbits. The specificities of the resulting antibodies were evaluated by immunoblotting. Antibodies purified from these sera by their affinity for brain kinesin react with a polypeptide of '~120 kD in extracts from bovine brain, PtK~ cells, and mouse neuroblastoma cells. They bind to a pair of polypeptides of '~120 kD present in crude kinesin prepared from Xenopus eggs and with a single polypeptide of ",,115 kD in extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
49
2

Year Published

1988
1988
2004
2004

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(53 citation statements)
references
References 35 publications
2
49
2
Order By: Relevance
“…6B, lane 4; bottom), and found that XStau is also coimmunoprecipitated with kinesin. The SUK4 antibodies recognize conventional kinesin heavy chain (Ingold et al, 1988;Neighbors et al, 1988;Sawin et al, 1992), suggesting that the XStauassociated kinesin is kinesin I. These results indicate that XStau is associated with a kinesin motor, which may provide a mechanism for active transport of late pathway RNAs.…”
Section: Xstau Is Associated With a Kinesin Motormentioning
confidence: 62%
“…6B, lane 4; bottom), and found that XStau is also coimmunoprecipitated with kinesin. The SUK4 antibodies recognize conventional kinesin heavy chain (Ingold et al, 1988;Neighbors et al, 1988;Sawin et al, 1992), suggesting that the XStauassociated kinesin is kinesin I. These results indicate that XStau is associated with a kinesin motor, which may provide a mechanism for active transport of late pathway RNAs.…”
Section: Xstau Is Associated With a Kinesin Motormentioning
confidence: 62%
“…Consistent with this role, kinesin accumulates at nerve ligations at fast transport rates along with membranous components of axonal transport (Dahlstrom et al, 1991;Hirokawa et al, 1991;Morin et al, 1993). However, descriptions exist of kinesin immunoreactivity with a diffuse distribution (Neighbors et al, 1988) and there are suggestions that the bulk of cellular kinesin is soluble (Hollenbeck, 1989).…”
Section: Introductionmentioning
confidence: 82%
“…In addition, polyclonal and monoclonal myosin antibodies have been used to inhibit the actin activated ATPase activity of myosin, (Mabuchi and Okuno, 1977;Kiehart and Pollard, 1984b;Peltz et al, 1985) to block myosin-driven motility in vitro (Kiehart and Pollard, 1984b;Flicker et al, 1985) to examine the relationship between myosin polymerization and ATPase activity as well as to probe the conformation and polymerization state of myosin (Citi and KendrickJones, 1987). Inhibitor myosin antibodies have provided evidence for the role of myosin in actin-based organelle transport (Adams and Pollard, 1986) and in cytokinesis (Mabuchi and Okuno, 1977;Kiehart et al, 1982).Kinesin antibodies have been used to establish immunological relatedness between kinesin from various cell types, as well as to identify, purify, and localize their corresponding antigens (Scholey et al, 1985;Vale et al, 1985b;Porter et al, 1987;Leslie et al, 1987;Saxton et al, 1988;Kuznetsov et al, 1988;Neighbors et al, 1988). However, none of these antikinesins was reported to inhibit kinesin activity.…”
mentioning
confidence: 99%
“…Kinesin antibodies have been used to establish immunological relatedness between kinesin from various cell types, as well as to identify, purify, and localize their corresponding antigens (Scholey et al, 1985;Vale et al, 1985b;Porter et al, 1987;Leslie et al, 1987;Saxton et al, 1988;Kuznetsov et al, 1988;Neighbors et al, 1988). However, none of these antikinesins was reported to inhibit kinesin activity.…”
mentioning
confidence: 99%